Use of social media by political parties of India in comparison of EU. - Ansari, Mohd Danish (2021)
This thesis focuses on the activities and engagement of political parties on social media platforms. Different approaches and ways of using social platforms by political parties will show us the position of social media and the trust of the public on social media in their countries. As the use of social media is increasing day by day we can easily see that government bodies, political parties and politicians are actively using these platforms. An increasing number of fans and followers on their official political accounts as well as on their official individual account speak the truth that they are trying really well to attract the user of social media towards them in their country.